MEGA biocentric software for sequence and phylogenetic analysis: a review. (8th July 2010) - Sohpal, Vipan Kumar; Dey, Apurba; Singh, Amarpal
Biocomputing has moved into central position in molecular biology research. Enormous improvements in genetic engineering have led to the accumulation of a vast amount of biological information. With the advent of this extensive repertoire of raw sequence information, the next major challenge for a modern researcher is to interpret this biological information. Molecular Evolutionary Genetic Analysis (MEGA) is bio-computational software to fill the vacuum between data development and analysis. In this paper, an attempt to review the evolution of MEGA software, working and application has been made. Moreover, data analysis, implementation and advantages over other bioinformatics software have been discussed systematically.